The relevance of career counselling in higher education: a study following students at a South African university - Lewis, Christine (Rhodes University, Faculty of Humanities, Department of Psychology)
Very few students in South Africa (SA) receive adequate career counselling at school and often arrive at institutions of higher learning without a clear sense of what their prospective careers will entail. The limited access to career counselling and assessment is further compounded by criticisms of popular career assessment instruments used in SA, where the primary goal of career counselling and assessment is to match clients to careers for job placement. This approach no longer serves the needs of a diverse SA population and disregards contextual influences on careers. Therefore, a need exists to understand and inform career counselling interventions and to guard against the provision of de-contextualised and contextually insensitive approaches. Moreover, changes in the workplace, where career change has become the norm as the world of work has moved away from stability and permanency to fluidity, calls for a contemporary response from career counselling theories, practitioners as well as researchers, to equip clients with the necessary skills to respond to these changes. Thus, SA institutions of higher learning need to innovate their practices to more inclusively, effectively, and justly serve the needs of a diverse student population for work success in a developing nation and a complex world. This study aimed to evaluate the relevance and effectiveness of a university's career counselling services from the students' perspectives. It focuses on gaining an indication of the perceived effectiveness of assessment measures used, and to ascertain the influences that impact on individual students' career decision-making over the course of undergraduate studies. Due to the increasing recognition for the need to develop a contextualised approach to career development interventions, this study included the SACII, a locally developed interest inventory as part of a career assessment battery, with a group of university students. A pragmatic approach using mixed-methods was used. Multiple case studies of the career trajectories of a cohort of undergraduate students who had undertaken career assessments at the university career centre, were tracked longitudinally over the course of undergraduate studies. Data were generated through vignettes that included the 13 participants' career assessment reports, a service evaluation questionnaire and two successive follow-up interviews. Each participant's first follow-up interview occurred six months after their career assessment feedback session; and the second follow-up was in the final year of undergraduate studies, after eighteen months. Descriptive statistical analysis summarised the basic features of the quantitative data from the evaluation questionnaire. Thematic analysis was used for organisation and analysis of the follow-up interview data. Findings were that the career counselling and assessment facilitated greater self-knowledge in relation to career decision-making, assisted with selecting degree major subjects and enhanced career planning abilities. Using locally developed assessment measures in career counselling proved to be useful. Exploring career development from an overarching developmental contextual framework that is applicable and well-suited to the SA context provided a deeper understanding of contextual influences that impact on students' career decision-making processes.
Keywords: Vocational guidance -- South Africa; Counseling in higher education -- South Africa; Identity (Psychology) in education; Ethnopsychology; College students -- South Africa Longitudinal studies